PERAN PROJECT MANAGER DAN ACCOUNT EXECUTIVE DALAM STRATEGI BRANDING “COOL ENOUGH” UNTUK PENINGKATAN BRAND AWARENESS DAN BRAND ASSOCIATION DI SMOOLY SEMARANG - Farah Syifa Fauzia Farah Syifa Fauzia; Muhammad Bayu Widagdo (Interaksi Online, 2026)
The problem faced by the Smooly brand in Semarang is the low level of brand awareness and brand association as a healthy beverage brand. Based on a survey of 200 respondents, only 30.5% of respondents were aware of the Smooly brand and most of them did not understand the brand value that emphasizes concern for health. This condition indicates that the previous communication strategy had not been optimal. This project aims to increase Smooly’s brand awareness and brand association through the “Cool Enough” campaign. This study uses the theoretical framework of Brand Equity, Brand Commutation, and the AISAS model to explain the communication process in the digital era. The method used in this project is the implementation of communication programs through social media management and event management. In its implementation, the roles of the Project Manager and Account Executive include planning, maintaining relationships with external stakeholders, coordinating the team, and supervising the execution of the campaign. The results of the campaign show an increase in social media reach, audience engagement, and a stronger consumer perception of Smooly as a brand that supports a healthy lifestyle. The campaign successfully increased brand awareness from 30.5% to 71%, representing an increase of 40.5 percentage points. Therefore, the “Cool Enough” campaign is considered effective in supporting the improvement of brand awareness and brand association of Smooly in Semarang.